Ancient pigment to treasure: Prussian blue as a cheap solid cyanide/nitrogen dual-source affording the high-yield syntheses of pricey endohedral clusterfullerenes. Issue 7 (3rd February 2021) - Xin, Jinpeng; Jin, Fei; Guan, Runnan; Chen, Muqing; Xie, Xiao-Ming; Zhang, Qianyan; Xie, Su-Yuan; Yang, Shangfeng
Abstract : Prussian blue was applied for the first time as a cheap solid cyanide/nitrogen dual-source, affording simplified yet high-yield simultaneous syntheses of novel dysprosium-based metal cyanide clusterfullerenes and metal nitride clusterfullerenes. Abstract : Endohedral clusterfullerenes featuring the encapsulation of metal clusters within carbon cages exhibit intriguing physical and chemical properties inaccessible to empty fullerenes. Thus far, their syntheses are predominantly fulfilled by using gaseous sources, suffering from low yield, and requiring an additional gas inlet and a heating pretreatment up to 1000 °C. Herein, we employ an ancient pigment, Prussian blue (Fe4 [Fe(CN)6 ]3 ), as a cheap solid cyanide/nitrogen dual-source, affording the simplified yet high-yield simultaneous syntheses of novel dysprosium (Dy)-based metal cyanide clusterfullerenes (CYCFs) DyCN@C2 n and metal nitride clusterfullerenes Dy3 N@C2 n . Surprisingly, the (CN) − anion of Fe4 [Fe(CN)6 ]3 survives under the extremely high temperature (up to 4000 K) of plasma generated via DC-arc discharge, and functions as the cyanide source of CYCFs. Under the optimized Dy : [CN] : C molar ratio of 1 : 1 : 15, the sum yield of isolated DyCN@C2 n (2 n = 76, 82) CYCFs produced using Fe4 [Fe(CN)6 ]3 is about 2.8 times higher than that obtained using gaseous N2 source. Moreover, the molecular structures of the three isomers of DyCN@C82 are unambiguously determined by single-crystal X-ray diffraction, indicating that the encapsulated triangular DyCN cluster is tunable due to strong metal–cage interactions. This study paves the way for the low-cost and high-yield syntheses of pricey endohedral fullerenes.